1999
DOI: 10.1093/humrep/14.11.2731
|View full text |Cite
|
Sign up to set email alerts
|

The idiopathic forms of premature menopause and early menopause show the same genetic pattern

Abstract: Genetic factors may influence the timing of menopause. Premature ovarian failure (POF) has recently been identified as a genetic entity, but no genetic data are available on early menopause (EM). We investigated 36 patients with EM (age of menopause between 40 and 45 years of age) using cytogenetic and pedigree analysis. In 30 patients of this study the EM was idiopathic and 15 subjects (50%) had a familial condition of EM or POF. Pedigree analysis revealed a dominant pattern of inheritance of EM through mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 14 publications
0
31
0
3
Order By: Relevance
“…However, this does notexclude the interest in searching other clinical POF cases within the family or relatives who presented early menopause, between 40 and 45 years. Indeed, some studies suggest that POF and early menopause show the same genetic features and that these conditions may be a variable expression of the same genetic disease (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does notexclude the interest in searching other clinical POF cases within the family or relatives who presented early menopause, between 40 and 45 years. Indeed, some studies suggest that POF and early menopause show the same genetic features and that these conditions may be a variable expression of the same genetic disease (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] In our study, limiting natural menopause, 1.1% of females reported to menopause <40 years, same as former studies, and they had significantly higher risk of death than those reported to menopause 45-49 years. A wide spectrum of pathogenic mechanisms may lead to the development of POF including chromosomal, 26 genetic, 27,28 autoimmune, 29,30 metabolic, 31 infectious, [32][33][34] and iatrogenic causes. 35,36 It may result in the higher mortality on early menopausal biased reporting of age at menopause unlikely.…”
Section: Femalesmentioning
confidence: 99%
“…This is supported by the observation that women with early menopause and POF are found within the same families, suggesting a genetic relationship between early menopause and POF (15,21).…”
mentioning
confidence: 52%